Pandangan Yuridis Terhadap Perdagangan Barang Bekas yang di Hubungkan dengan Peratuan Perlindungan Konsumen - Mahmudi, Afrizal; Guntara, Deny; Abas, Muhamad (Universitas Ekasakti, 2024)
This study reviews the legal perspective on the sale of second-hand goods in thrift markets in the city of Bandung, based on Law No. 7 of 2014 concernings Trades and Law No. 8 of 1999 concerning Consumers Protection. A combined empirical and normative juridical approach is used with diverse data. The focus of the research is on consumer protection in purchasing second-hand clothing and the responsibilitys of businesses for the products they sell. According to Law No. 8 of 1999 on Consumer Protection, the government is responsible for supervision and guidance to protect consumers, while businesses are responsible for ensuring the safety and quality of the products offered. This research faces data limitations but provides valuable contributions to understanding the trade of second-hand goods and lays the groundwork for further policy discussions. Future research could focus on implementing laws in the trade of second-hand goods in various regions, both in thrift and online markets, for a deeper understanding of their application. This study holds significant originality in enriching understanding of the law, second-hand trade, and consumer protection, and contributes positively to the development of a fair and sustainable society.